1995
DOI: 10.1093/jmedent/32.6.751
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Age of Ixodid Ticks: Aspects of Its Determination and Application

Abstract: This review analyzes 30 yr of data concerning physiological age of ixodid ticks. The level and state of nutritional reserves in unfed ticks has been proposed as an index of tick physiological age. The dynamics of the use of these substances reflect tick aging. Thus, physiological age of ixodid ticks is determined by estimating the irreversible changes caused by natural vital activity in the body of unfed ticks, which inevitably raises the probability of tick death. The 4 age groups used in most studies corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…It was observed that fat content in Þeld-collected females was slightly higher than that in Þeld-collected males and considerably higher than that in Þeld-collected nymphs. These results are in line with what is expected because fat content is a source of energy derived from each bloodmeal (Uspensky 1995). Larvae, which ingest less blood than further developmental stages (Ogden et al 1998), contain less fat than adults as they molt into nymphs.…”
Section: Discussionsupporting
confidence: 83%
“…It was observed that fat content in Þeld-collected females was slightly higher than that in Þeld-collected males and considerably higher than that in Þeld-collected nymphs. These results are in line with what is expected because fat content is a source of energy derived from each bloodmeal (Uspensky 1995). Larvae, which ingest less blood than further developmental stages (Ogden et al 1998), contain less fat than adults as they molt into nymphs.…”
Section: Discussionsupporting
confidence: 83%
“…Reduction in hemoglobin levels seems to reflect a steady aging of ticks and can serve as a good indicator of their physiological age. 31 The level and state of nutritional reserves in unfed ticks have been proposed as an index of tick physiological age. Physiological age, which is an independent parameter in each of the active developmental stages in arthropods, has been well studied in medical entomology.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some materials that can inhibit starvation-induced autophagy might be effective as antitick or transmission-blocking drugs because tick susceptibility to acaricides seems to be shown to increase with tick age. 31 Further research into the molecular mechanism and the physiological significance of autophagy may contribute to the development of new methods for controlling ticks and tick-borne protozoa including Babesia and Theilelia parasites.…”
Section: Discussionmentioning
confidence: 99%
“…This goes for the physiological age based on histological observations ( BAL-ASHOV 1961 as cited by USPENSKY 1995), which currently is recognized to be the most appropriate method for determination of physiological age and for the method based on anatomical features. The anatomical and other methods have however been found to be comparable to the histological method for several tick species including I. ricinus (USPENSKY 1995). For the individual tick, the observed age gives an assessment of a physiological status in terms of reserve nutrition, which in general corresponds to the physiological age.…”
Section: Determination Of Physiological Agementioning
confidence: 97%
“…Physiological age has been successfully used in several studies to describe the physiological status of the individual Ixodes species (USPENSKY 1995). Although other methods of establishing a physiological parameter may be used, e.g., remaining fat or fertili-…”
mentioning
confidence: 99%